Mental Health Challenges Among Filipino Special Education Teachers in Clark County, Las Vegas, Nevada, USA (American Journal of Arts and Human Science, 2024)
This study examines the mental health and demographics of Filipino special education teachers in Clark County, Las Vegas. Using a cross-sectional design, data from 60 teachers were collected through a structured questionnaire, including the Mental Health Analysis by Thorpe and Clark. Findings reveal that many teachers have low levels of close relationships (61.67%) and social participation (65.00%), indicating social support and isolation issues. Logistic regression shows that male teachers and those aged 30-39 are more likely to have strong close relationships. The results highlight the need for tailored interventions to enhance social relationships and support systems, especially for female teachers and those outside the 30-39 age range.